Educación y comunicación en la Retórica de Aristóteles - Pascual, L.C., Fernando (Alpha Omega, 2019)
Summary: The study on communication in Aristotle’s Rhetoric allows us to evidence numerous elements of continuity regarding Plato’s thought in what refers to the theory on dialogue. Aristotle, in his Rhetoric, attentively analyzes the three main characteristics of all human communication: the person who speaks, the person who listens and what is said. He notes how the central element is the search of persuasion, around which educational relationship revolves. Experience, which most effectively helps to prepare the speech is also very important, and searching study on lógos, éthos and páthos becomes necessary in the area of all dialogic relationship. Keywords: Aristotle, Plato, rhetoric, communication, education, persuasion. Palabras clave: Aristóteles, Platón, retórica, comunicación, educación, persuasión.